PENGARUH PARAMETER FISIKA DAN KIMIA TERHADAP KEHADIRAN IKAN LOMPA (Thryssa baelama Forsskål) DI PERAIRAN PANTAI APUI KABUPATEN MALUKU TENGAH - Meillisa Carlen Mainassy (Jurnal Perikanan Universitas Gadjah Mada, 2017)
Maluku is one of the archipelago province in Indonesia that has small pelagic fish resources with widespread distribution, such as lompa (Thryssa baelama Forsskål). One of lompa habitat in Mollucas is in Apui coastal areas. The presence of lompa depends on physical and chemical parameters in the waters. This study aims to determine the influence of physical and chemical parameters on the presence of lompa in Apui coastal area Central Mollucas. This study was conducted in June - July 2015. This research is ex-post facto using the value of Environmental Water Quality Index which refers to US-National Sanitation Foundation-Water Quality Index (NSF-WQI). Physical and chemical parameters measured include temperature, velocity, depth, brightness, salinity, pH and dissolved oxygen. The results of calculations with the Indeks Mutu Lingkungan Perairan (IMLP) are 95.61; 92,15; 88.61; 96,37; 93,76; 79.57. And the results of lompa fishing were 181, 162, 205, 173, 184, and 97 respectively. The research conclusion is that the Apui coastal areas are in good condition and potential as lompa habitat.